Covid-19 attacks the body of purchasing and supply management: A medical check of the immune system. Issue 4 (October 2021) - Glas, Andreas H.; Meyer, Matthias M.; Eßig, Michael
Abstract: Much like the immune system of the body, the 'immune system' of purchasing and supply management (PSM) is also affected by the Covid-19 virus. Medicine must hinder the spread of the virus and outbreak of disease, just as PSM must prevent risk events and handle supply disruptions. The existing debate on supply resilience and robustness can be demonstrated using this medical analogy. The purpose of this article was to perform a medical check of the 'PSM immune system' to identify lessons and research gaps when confronted with a low-frequency-high-impact event such as the pandemic. As a provocative note, this article identifies research gaps in elements of the immune system of PSM (e.g., helper cells – consultancy support or memory cells – feedback loops). The results call for a more holistic debate on the immune system of PSM. Two approaches for research on 'conventional' or 'alternative' risk management schools of thought are presented as a basis for future discourse on how to improve the PSM immune system. Highlights: Covid-19 leads to severe supply disruptions, thus the aim is to check the ability of PSM to respond. The elements of supply risk management are mapped onto components of the body's immune system. The medical analogy reveals seven research gaps in PSM risk management. For example, a discussion on memory cells is missing, calling for future research on better learning. Future discourse shall consider not only conventional, but also alternative risk management approaches.